THE EFFECT OF PRODUCT QUALITY AND PROMOTION ON PURCHASE DECISIONS MEDITED CONSUMER SATISFACTION ON MSMES IN LAMONGAN REGENCY - Rachmawati, Adinda Dwi; Muhtarom, Abid; Efendi, Yuhronur; Yaskun, Mohammad; Suprapto, Hery (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
In Indonesia, the business sector that has progressed is MSMEs. MSMEs have an impact on economic recovery. This study aims to determine product quality and promotion of purchasing decisions mediated by consumer satisfaction at UMKM Lamongan Regency. Researchers used quantitative methods with a sample of 316 respondents. The data analysis used is the SEM method with the Smart PLS version 3.0 tool. The test used consists of the outer model, inner model, mediation test and hypothesis testing. The variables of product quality, promotion, purchasing decisions and consumer satisfaction have been declared valid and reliable. Product quality and promotion variables on purchasing decisions mediated by consumer satisfaction are referred to as Partial Mediation. Product quality and promotion variables have a positive and significant impact on purchasing decisions.